2016
DOI: 10.1007/s10995-016-2010-4
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Well-Being: Structural Analyses of Latina Mothers by Nativity

Abstract: Objective This study examined the direct and mediating effects of maternal social capital on health and well-being for native- and foreign-born Latina mothers and their children. Methods Data were drawn from the baseline and nine-year follow up waves of the Fragile Families and Child Well-being Study. The study included a sample of 874 Latina mothers. Mplus7 was used to perform structural equation modeling to determine whether exogenous indicators (age, education, and economic well-being) predicted social capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Previous work has found that children of US-born Latinas with depression have poorer developmental outcomes than foreignborn Latinas [40]. Social capital has been found to improve maternal health of foreign-born Latina women [41]. Moreover, there is evidence of Latina paradox in some situations, where babies born to US-born Latina women face similar outcomes to Whites while babies of foreign-born Latinas have better outcomes in terms of prematurity and birthweight [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has found that children of US-born Latinas with depression have poorer developmental outcomes than foreignborn Latinas [40]. Social capital has been found to improve maternal health of foreign-born Latina women [41]. Moreover, there is evidence of Latina paradox in some situations, where babies born to US-born Latina women face similar outcomes to Whites while babies of foreign-born Latinas have better outcomes in terms of prematurity and birthweight [42].…”
Section: Discussionmentioning
confidence: 99%
“…Using the Fragile Families and Child Well-being Study and the UK Millennium Cohort Study, they found that foreign born mothers in both the US and the UK had healthier behaviors than their native-born counterparts, including both socioeconomically disadvantaged and advantaged mothers (Jackson et al, 2012). Held and Cuellar (2016) examined nativity in Latinas mothers (n = 874) using the year nine follow up from the Fragile Families and Child Well-being Study. For foreign-born Latinas (n = 334), social capital was a significant predictor of maternal well-being but not for native born Latinas (n = 540).…”
Section: Birthplace/nativitymentioning
confidence: 99%
“…For foreign-born Latinas (n = 334), social capital was a significant predictor of maternal well-being but not for native born Latinas (n = 540). However, social capital significantly mediated the effects of age, education, and eco-nomic well-being on maternal well-being for both native and immigrant Latinas, suggesting that social capital serves as a protective factor for better health for Latinas regardless of birthplace (Held & Cuellar, 2016). Immigrants rely heavily on social networks and other former immigrants to secure necessities (e.g.…”
Section: Birthplace/nativitymentioning
confidence: 99%
See 1 more Smart Citation
“…Residents who believe their SC is low are more likely to report poor mental health than their counterparts. However, SC also has a protective effect on mothers’ well-being ( Mulvaney and Kendrick, 2005 ; Held and Cuellar, 2016 ). Research on the relationship between SC and PPD has been conducted in different countries.…”
Section: Introductionmentioning
confidence: 99%